INCREASE PRODUCTION VOLUME BY REGENERATION OF COTTON - Bakhritdinov, Saifitdin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Cotton fiber is one of the main products of the textile industry in the world. Research work is carried out aimed at delivering raw cotton to processing processes while preserving its natural parameters and developing new scientific and technical solutions for resource-saving technologies and technical means. In this regard, priority is given to research on the technology of preliminary processing of cotton, cleaning cotton from small and large impurities, efficient organization of cotton processing, and the development of energy-saving technologies. At the same time, special attention is paid to the development of technical solutions that eliminate problems and increase the efficiency of all technological processes.